Embolized Stems Recover Overnight in Zea mays: The Role of Soil Water, Root Pressure, and Nighttime Transpiration - Gleason, Sean M.; Wiggans, Dustin R.; Bliss, Clayton A.; Young, Jason S.; Cooper, Mitchell; Willi, Katie R.; Comas, Louise H. (Frontiers in Plant Science, 2017)
It is not currently well-understood how much xylem conductance is lost in maize plants during the day, if conductance is recovered during the night, or what soil water conditions are required for recovery to take place. To answer these questions we designed a greenhouse experiment whereby two genetically dissimilar maize genotypes were subjected to a level of water stress commonly experience in the field (Ψxylem ~ -2 MPa). We then measured the loss of stem conductance associated with this level of stress, as well as the overnight recovery following three re-watering treatments: Ψsoil ~ 0 MPa, Ψsoil ~ -0.40 MPa, and Ψsoil ~ -1.70 MPa. Midday leaf water potentials of -1.98 MPa resulted in stem-specific conductivity (KS) values that were 31.5% of maximal (i.e., 68% loss). Returning soils to field capacity (Ψsoil ~ 0 MPa) overnight allowed for the significant recovery of KS (76% of maximal), whereas partial watering (Ψsoil ~ -0.40 MPa) resulted KS values that were 51.7% of maximal values, whereas not watering resulted in no recovery (35.4% of maximal; Ψsoil ~ -1.7 MPa). Recovery of KS was facilitated by the generation of root pressure and low rates of nighttime transpiration.